RELIABILITY OF GLULAM BEAMS SUBJECTED TO BENDING (Advances in Civil and Architectural Engineering, 2021)
This paper presents probabilistic reliability analyses of glulam beams by using level I semiprobabilistic procedure according to Eurocode standards and level II first-order reliability method. The analyses were performed for normal design situations on two groups of girders: roof and ceiling girders. The girders were first dimensioned for the ultimate limit state of bending according to Eurocode 5, after which the limit state equations were set with stochastic values of basic variables. A sensitivity analysis showed that the effect of strength variation is not significant when the coefficient of strength variation is approximately 15%: the recommended value from previous literature. The reliability indices obtained in this study are compared with the corresponding standard values for structural categories RC2 and RC3 according to Eurocode 0.